A Facile Self‐Templated Approach for the Synthesis of Pt Hollow Nanospheres with Enhanced Electrocatalytic Activity. Issue 20 (1st September 2016) - Li, Fu‐Min; Zhai, Ya‐Nan; Wu, Zhu‐Qing; Li, Shu‐Ni; Lee, Jong‐Min
Abstract : In this work, the well‐defined Pt hollow nanospheres with the rough porous surface are synthesized by a facile self‐templated approach. The formation of the spherical Pt(II)‐urea complex plays a key role in the generation of Pt hollow nanospheres. Sodium formate is employed as the suitable reducing agent for reducing Pt(II)‐urea complexes. The hollow structure and the rough porous surface with abundant atomic defects are confirmed by scanning electron microscopy and transmission electron microscopy, respectively. The CO‐stripping experiment reveals that these abundant atomic defects effectually enhance the electrocatalytic activity of the Pt hollow nanospheres for the CO oxidation reaction. Moreover, the low activation energy of the ethanol oxidation reaction (EOR) on the Pt hollow nanospheres indicates that the hollow structure and the rough porous surface are beneficial kinetically for the EOR in alkaline media. Compared with commercial Pt black, the as‐prepared Pt hollow nanospheres show the enhanced electrocatalytic activity and stability for the EOR in alkaline media. In view of the enhanced catalytic activity and the facile self‐templated approach, the Pt hollow nanospheres may be a new promising electrocatalyst for alkaline direct ethanol fuel cells. Abstract : Well‐defined Pt hollow nanospheres with a rough surface are successfully synthesized by a facile self‐templated approach.